Archeologia i świadomość historyczna - Kmieciński, Jerzy (Zeszyty Wiejskie, 2014)
Archeology as a social science has been constantly striving since the 19th century to make material historical testimonies of all inhabited areas of the globe more available. It leads to the improvement and consolidation of systematic, chronological and chorological system and as a result to obtain a deepened insight into culture and into specific aspects of history of individual human communities. These penetrations are of diverse breadth and depth. The broadest and the deepest ones are observed in highly developed cultures, the least spectacular ones are noted in case of wandering hunting communities whose traces are only stone tools made in a hurry.